Cucurbitacin mediated regulation of deregulated oncogenic signaling cascades and non-coding RNAs in different cancers: Spotlight on JAK/STAT, Wnt/β-catenin, mTOR, TRAIL-mediated pathways. (August 2021) - Lin, Xiukun; Farooqi, Ammad Ahmad
Abstract: Research over decades has enabled us in developing a better understanding of the multifaceted and heterogeneous nature of cancer. High-throughput technologies have helped the researchers in unraveling of the underlying mechanisms which centrally regulate cancer onset, metastasis and drug resistance. Our rapidly expanding knowledge about signal transduction cascade has added another layer of complexity to already complicated nature of cancer. Deregulation of cell signaling pathways played a linchpin role in carcinogenesis and metastasis. Cucurbitacins have gained tremendous attention because of their remarkable pharmacological properties and considerable ability to mechanistically modulate myriad of cell signaling pathways in different cancers. In this review, we have attempted to provide a mechanistic and comprehensive analysis of regulation of oncogenic pathways by cucurbitacins in different cancers. We have partitioned this review into separate sections for exclusive analysis of each signaling pathway and critical assessment of the knowledge gaps. In this review, we will summarize most recent and landmark developments related to regulation of Wnt/β-catenin, JAK/STAT, mTOR, VEGFR, EGFR and Hippo pathway by cucurbitacins. Moreover, we will also address how cucurbitacins regulate DNA damage repair pathway and TRAIL-driven signaling in various cancers. However, there are still outstanding questions related to regulation of SHH/GLI, TGF/SMAD and Notch-driven pathway by cucurbitacins in different cancers. Future studies must converge on the analysis of full-fledge potential of cucurbitacins by in-depth analysis of these pathways and how these pathways can be therapeutically targeted by cucurbitacins.